2019
DOI: 10.3390/polym11111795
|View full text |Cite
|
Sign up to set email alerts
|

Wasted Ganoderma tsugae Derived Chitosans for Smear Layer Removal in Endodontic Treatment

Abstract: The objective of this study is to investigate the synergistic effects of acid etching and metal-ion chelation in dental smear layer removal using wasted Ganoderma tsugae derived chitosans. The wasted Ganoderma tsugae fruiting body was used to prepare both acid-soluble fungal chitosan (FCS) and alkali-soluble polysaccharide (ASP). To explore the effective irrigant concentration for smear layer removal, a chelating effect on ferrous ions was conducted. Specimens of various concentrations of EDTA, citric acid, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The use of biological polymers from waste to produce new materials for medical use is a trend for sustainability. Since chitosan and its derivatives have been reported to be a material with high chelating capacity [17], Huang et al designed an irrigant system using chitosans derived from waste Ganoderma tsugae for smear layer removal in endodontic treatment and concluded that chitosan derived from fungal biomass shows potential as an alternate irrigant for clinical use [18]. Thacker et al's study testing physical properties and cell response of artificial tears produced using Bletilla striata polysaccharide is another example of natural plant-based polymers with tissue engineering applications.…”
mentioning
confidence: 99%
“…The use of biological polymers from waste to produce new materials for medical use is a trend for sustainability. Since chitosan and its derivatives have been reported to be a material with high chelating capacity [17], Huang et al designed an irrigant system using chitosans derived from waste Ganoderma tsugae for smear layer removal in endodontic treatment and concluded that chitosan derived from fungal biomass shows potential as an alternate irrigant for clinical use [18]. Thacker et al's study testing physical properties and cell response of artificial tears produced using Bletilla striata polysaccharide is another example of natural plant-based polymers with tissue engineering applications.…”
mentioning
confidence: 99%